2014
DOI: 10.1002/mnfr.201300821
|View full text |Cite
|
Sign up to set email alerts
|

The capsaicin analog nonivamide decreases total energy intake from a standardized breakfast and enhances plasma serotonin levels in moderately overweight men after administered in an oral glucose tolerance test: A randomized, crossover trial

Abstract: Addition of 0.15 mg nonivamide to a glucose solution reduced ad libitum energy intake from a standardized breakfast in moderately overweight men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 40 publications
(57 reference statements)
3
29
1
1
Order By: Relevance
“…The performance of an oral glucose tolerance test has been evaluated as a suitable tool to investigate the ghrelin secretion in humans . Our data indicate that HED exerts its appetizing effects only when it is administered in combination with a caloric load.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The performance of an oral glucose tolerance test has been evaluated as a suitable tool to investigate the ghrelin secretion in humans . Our data indicate that HED exerts its appetizing effects only when it is administered in combination with a caloric load.…”
Section: Discussionmentioning
confidence: 95%
“…Volunteers consumed the breakfast until satiation. The remaining food was weighed, and ad libitum energy intake as well as macronutrient intake was calculated by means of the German Food code and nutrient data base `Bundeslebensmittelschlüssel BLS II’ according to Hochkogler et al…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The meal comprised four rolls, four slices of dark bread, four slices of ham and cheese, 100 g honey and strawberry jam, 80 g butter, 180 g berry yogurt, 50 g coffee cream, 20 g sugar as well as 200 mL of coffee or tea and water as desired. The quantity consumed was determined by weighing the remaining food, in order to calculate the ad libitum energy and macronutrient intake using the German Food Code and nutrient database “Bundeslebens mittelschlüssel,” according to Hochkogler et al . Apart from assessing the potential impact on satiation, which determines the size of a meal, participants were asked to document their diet using provided forms by estimating their food intake on both study days for 24 h post‐intervention to evaluate an influence on satiety, describing the inter‐meal period following the end of an eating episode .…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, ghrelin, glucagon‐like‐peptide1 (GLP‐1), PYY 3–36 , and serotonin concentrations were measured in the plasma as orexigenic and anorexigenic markers. The crossover study design in this short‐term intervention trial was conducted based on previous works which reported an impact of other aroma active food constituents on food intake and hormonal regulation of satiety …”
Section: Introductionmentioning
confidence: 99%